INNOVATIONS AND ADVANCED FOREIGN EXPERIENCES IN TEACHING MODERN INFORMATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Akhmedova Zebikhan Siddikovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes innovations and advanced foreign experiences in the teaching of modern information technologies in the higher education system, as well as the views of our country's and foreign scientists on pedagogical innovations. Advanced pedagogical technologies imply interactive teaching methods. These are discussion classes, negotiations, business games, educational projects, problem solving, case studies, etc. These methods help to increase the creative activity of students, solve economic issues, and find the most optimal ways to solve a problem.